Teaching Fractions through Situations: A Fundamental Experiment - Brousseau, Guy.; Brousseau, Nadine; Warfield, Virginia; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This work presents one of the original and fundamental experiments of Didactique, a research program whose underlying tenet is that Mathematics Education research should be solidly based on scientific observation. Here the observations are of a series of adventures that were astonishing for both the students and the teachers: the reinvention of fractions and of decimal numbers in a sequence of lessons and situations that permitted the students to construct the concepts for themselves. The book leads the reader through the highlights of the sequence's structure and some of the reasoning behind the lesson choices. It then presents explanations of some of the principal concepts of the Theory of Situations. In the process, it offers the reader the opportunity to join a lively set of fifth graders as they experience a particularly attractive set of lessons and master a topic that baffles many of their contemporaries.
1. The Adventure of the Students -- 2. Viewing the Adventure from the Perspective of Teachers and Researchers -- 3. Some Key Concepts and Terms from the Theory of Situations -- 4. The Setting for the Adventure -- 5. Description of the Center for Observation for Research in Mathematics Education -- 6. Conclusions and future directions.
Keywords: Education; Mathematics; Education; Mathematics Education; Applications of Mathematics; Mathematics, general; Learning & Instruction